Antiradical activity of isoquinoline and indole alkaloids - Pérez, Pilar; González, Alejandro; Sousa, Luís; Camejo, David; Castillo, Jimmy; Hasegawa, Masahisa; Rodríguez, María (Ciencia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Helvetica; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:7 0 0 0 147 0; @font-face font-family:Bookman; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-alt:"Bookman Old Style"; mso-font-charset:0; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:0 0 0 0 0 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The antiradical activity of four alkaloids -ibogaine, voacanginol, boldine and berberine- were studied. The relationship between their antiradical activities and structural aspects was investigated. The antiradical activity was tested in ethanolic solution as the ability to scavenge free 1,1”™-diphenyl-2-picrylhydrazyl radicals (DPPH). The lowest energy molecular conformations and electrostatic potential of the alkaloids were calculated using HyperChem molecular modeling software. Three compounds ibogaine, voacanginol and boldine bear abstractable hydrogen on their structures; the main difference between them is the presence of phenolic hydrogen in boldine and labile hydrogens linked to nitrogen atoms in ibogaine and voacanginol, two closely related alkaloids. The alkaloid tested boldine showed similar activity to voacanginol and ibogaine, whereas berberine, lacking an abstractable hydrogen in its structure, showed the lowest antiradical activity.